Evaluative meaning in translation - Jurko, Primož (ELOPE (Ljubljana), 2015)
Evaluative meaning is frequently understood as a form of connotation, pertaining to single lexical items. However, the term has recently been applied also to longer stretches of text, spanning several words. The paper generally deals with the latter aspect and provides a corpus-driven analysis of several Slovene and English phrases that may appear semantically neutral, yet turn out to be heavily non-neutral in terms of their semantic properties. After a short introduction of the main approaches to the topic, including its dilemmas, the paper focuses on the L1-into-L2 translation of such strings, with particular emphasis on proper rendering of the evaluative meaning. While further research is warranted into the matter, the work presented here attests to the complex and ubiquitous nature of the Sinclairian extended unit of meaning.
Keywords: Corpus linguistics; korpusno jezikoslovje; leksikologija; lexicology; prevajanje; semantična prozodija; translation